NK Cell Priming From Endogenous Homeostatic Signals Is Modulated by CIS - Delconte, Rebecca B.; Guittard, Geoffrey; Goh, Wilford; Hediyeh-Zadeh, Soroor; Hennessy, Robert J.; Rautela, Jai; Davis, Melissa J.; Souza-Fonseca-Guimaraes, Fernando; Nunès, Jacques A.; Huntington, Nicholas D. (Frontiers in Immunology, 2020)
Natural killer (NK) cell activation is controlled by a balance of activating and inhibitory signals and cytokines such as IL-15. We previously identified cytokine-inducible SH2-containing protein (CIS) as a negative regulator of IL-15 signalling in NK cells under inflammatory conditions. While the functional effect of Cish-deficiency in NK cells was obvious by their increased anti-tumour immunity and hyper-proliferative response to IL-15, it remained unclear how CIS regulates NK cell biology in steady-state. Here, we investigated the role of CIS in the homeostatic maintenance of NK cells and found CIS-ablation promoted terminal differentiation of NK cells and increased turnover, suggesting that under steady-state conditions, CIS plays a role in maintaining IL-15 driven regulation of NK cells in vivo. However, hyper-responsiveness to IL-15 did not manifest in NK cell accumulation, even when the essential NK cell apoptosis mediator, Bcl2l11 (BIM) was deleted in addition to Cish. Instead, loss of CIS conferred a lower activation threshold, evidenced by augmented functionality on a per cell basis both in vitro and in vivo without prior priming. We conclude that Cish regulates IL-15 signalling in NK cells in vivo, and through the rewiring of several activation pathways leads to a reduction in activation threshold, decreasing the requirement for priming and improving NK cell anti-tumour function. Furthermore, this study highlights the tight regulation of NK cell homeostasis by several pathways which prevent NK cell accumulation when IL-15 signalling and intrinsic apoptosis are dysregulated.